2019
DOI: 10.1021/acs.chemrestox.8b00284
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of Titanium Dioxide Nanoparticles Is Mediated by Actin-Dependent Reorganization and Clathrin- and Dynamin-Mediated Endocytosis in H9c2 Rat Cardiomyoblasts

Abstract: Titanium dioxide nanoparticles (TiO2 NPs) are widely used for industrial and commercial applications. Once inside the body, they translocate into the bloodstream and reach different areas of the cardiovascular system including the heart, increasing the risk of developing cardiovascular diseases; consequently, the investigation of their interaction with cardiac cells is required. We previously showed that TiO2 NPs are internalized by H9c2 rat cardiomyoblasts, and here, we examined the molecular mechanisms under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Further, TiO 2 internalization is also mediated, to a lesser extent, by clathrin-dependent endocytosis and micropinocytosis. These results are supported by previous studies, which have shown that TiO 2 particle internalization is mediated by phagocytosis and endocytosis in glial cells [28], H9c2 rat cardiomyoblasts [27], and rodent macrophages [41,42]. The multiple uptake pathways of TiO 2 NPs may partially explain why they were internalized more efficiently and why they induce more robust cytotoxicity, oxidative stress, and inflammatory cytokines compared to Ta NPs under the same conditions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Further, TiO 2 internalization is also mediated, to a lesser extent, by clathrin-dependent endocytosis and micropinocytosis. These results are supported by previous studies, which have shown that TiO 2 particle internalization is mediated by phagocytosis and endocytosis in glial cells [28], H9c2 rat cardiomyoblasts [27], and rodent macrophages [41,42]. The multiple uptake pathways of TiO 2 NPs may partially explain why they were internalized more efficiently and why they induce more robust cytotoxicity, oxidative stress, and inflammatory cytokines compared to Ta NPs under the same conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Phagocytosis and endocytosis are responsible for the uptake and clearance of particles [27,40]. However, to date, the mechanistic nature of TiO 2 and Ta NP internalization 10 Mediators of Inflammation in human macrophages remains obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptor ligands that are internalized through receptor-mediated CME include low-density lipoprotein, transferrin, growth factor, G-protein, tyrosine kinase receptors and insulin [36] . Nanomaterials such as Ag and TiO 2 nanoparticles are also internalized by the endocytic pathways mediated by clathrin [37] , [38] .…”
Section: Endocytosis Mechanisms For Nanomaterialsmentioning
confidence: 99%
“…The clathrin-dependent pathway includes three key steps: cell membrane infolding that depends on clathrin, vesicle formation that relies on dynamin, and endosome maturation. To investigate the endocytic pathway of LBP, four specific inhibitors for receptor-mediated cellular endocytosis pathway were used, including Chloropromazine (preventing the assembly and disassembly of clathrin lattices on cell membrane and endosomes) [40], Dynasore (inhibiting dynamin activity) [41], Cytochalasin D (disrupting actin filaments and inhibiting actin polymerization) [42], Amiloride (Epidermal sodium channel blocker) [43]. The flow cytometry assay (Figure 4d) showed that compared with the cellular uptake in the control group, all the inhibitors showed different degrees of inhibitory effect on the internalization of LBP, and the order of inhibition intensity was Chloropromazine > Cytochalasin D > Dynasore > Amiloride.…”
Section: The Uptake Of Dye Labeled Lbp By Macrophagesmentioning
confidence: 99%